A novel bipartite antitermination system widespread in conjugative elements of Gram-positive bacteria. Issue 10 (17th May 2021) - Miguel-Arribas, Andrés; Val-Calvo, Jorge; Gago-Córdoba, César; Izquierdo, José M; Abia, David; Wu, Ling Juan; Errington, Jeff; Meijer, Wilfried J J
Abstract: Transcriptional regulation allows adaptive and coordinated gene expression, and is essential for life. Processive antitermination systems alter the transcription elongation complex to allow the RNA polymerase to read through multiple terminators in an operon. Here, we describe the discovery of a novel bipartite antitermination system that is widespread among conjugative elements from Gram-positive bacteria, which we named conAn . This system is composed of a large RNA element that exerts antitermination, and a protein that functions as a processivity factor. Besides allowing coordinated expression of very long operons, we show that these systems allow differential expression of genes within an operon, and probably contribute to strict regulation of the conjugation genes by minimizing the effects of spurious transcription. Mechanistic features of the conAn system are likely to decisively influence its host range, with important implications for the spread of antibiotic resistance and virulence genes. Graphical Abstract: